Peran etika bisnis Islam terhadap kinerja usaha mikro, kecil, dan menengah (UMKM) pangan di Kota Bogor - Salahuddin El Ayyubi; Sausan Anggi Anggraini (Journal of Business & Banking, 2016)
Micro, Small, and Medium Entreprises (MSMEs) have a very important role for developing and increasing Indonesia economy. MSMEs contribution on the Gross Domestic Product (GDP) up to 60.64% and supply manpower up to 97%. However, this potency still accompanied by violations that occurred mainly in the food sector. One of the reason is there are a lot of bussiness activity is not in accordance with proper business ethics. This study analyzes the role of Islamic business ethics on the MSMEs performance. Descriptive analysis method is used to analyze the entrepreneur perception on Islamic Bussiness Ethics, while role of Islamic business ethics on the performance of MSMEs is analyzed with Partial Least Square-Structural Equation Modelling (PLS-SEM). Primary data were collected through online questionnaires and deep interviews to food SMEs muslim businessmen in Bogor City. Results show that the Islamic bussiness ethics has a positive effect on the MSMEs performance.